[tex]\bold{\huge{\green{\underline{ Solution }}}}[/tex]
Let the present age of son be x
Therefore,
Present age of the father will be
[tex]\bold{ = 3x\:\: years }[/tex]
9 years ago,
The age of the son was
[tex]\bold{ = ( x - 9)\: years}[/tex]
Age of the father was
[tex]\bold{ = 3(x - 9) \:years ...eq(1)}[/tex]
But,
From eq(1) and eq(2) :-
[tex]\sf{3(x - 9) = 4(x - 9)}[/tex]
[tex]\sf{3x - 27 = 4x - 36}[/tex]
[tex]\sf{3x - 4x = -36 + 27}[/tex]
[tex]\sf{-x = -9 }[/tex]
[tex]\bold{\pink{ x = 9 \: years }}[/tex]
Thus, The present age of the son is 9 years
Age of the father will be
[tex]\sf{ = 3 × 9 }[/tex]
[tex]\bold{\red{ = 27 \: years }}[/tex]
Hence, The present ages of son and father is 9 years and 27 years